Exhaled markers of antioxidant activity and oxidative stress in stable cystic fibrosis patients with moderate lung disease. (20th February 2018) - Spicuzza, Lucia; Parisi, Giuseppe Fabio; Tardino, Lucia; Ciancio, Nicola; Nenna, Raffaella; Midulla, Fabio; Leonardi, Salvatore
Abstract: The sustained imbalance between oxidant and antioxidant species contributes to lung damage in patients with cystic fibrosis (CF). Glutathione (GSH) is an important component of the antioxidant defense in the airways epithelial lining fluid and its transportation out of the cells may be altered in CF. The aim of this study was to assess the oxidants/antioxidants balance in the airways of patients with CF. We measured the concentrations of GSH, the total antioxidant capacity and the concentration of 8-iso-prostaglandin F2 α (8-isoprostane), a marker of oxidative stress, in the exhaled breath condensate of 17 non-smoking patients with CF, in stable phase, and in 17 age-matched healthy subjects. The levels of GSH and total antioxidant capacity in patients with CF were significantly lower than in healthy subjects (0.66 ± 0.07 μ M versus 1.30 ± 0.08 μ M, p < 0.001, respectively for GSH; 0.157 ± 0.02 mM and 0.32 ± 0.01 mM, p < 0.05, respectively for antioxidant capacity). The concentration of 8-isoprostane was higher in CF than in healthy controls (26.5 ± 0.1 pg ml −1 versus 10.8 ± 0.1 pg ml −1 ; p < 0.05). A low concentration of antioxidant agents, particularly glutathione, and increased levels of 8-isoprostane in the exhaled breath suggest an altered oxidizing environment in the airways of patients with CF. This altered redox environment in the epithelial liquid surface may contribute to progressive lung disease.